How do you implicitly differentiate #ln(x/y)=x-y #?
It is
#d(lnx-lny)/dx=d(x-y)/dx=> 1/x-[(y')/y]=1-dy/dx=> dy/dx-dy/dx*[1/y]=1-1/x=> dy/dx=[1-1/x]/[1-1/y]#
By signing up, you agree to our Terms of Service and Privacy Policy
To implicitly differentiate the equation ( \ln\left(\frac{x}{y}\right) = x - y ), you follow these steps:
- Take the natural logarithm of both sides of the equation.
- Differentiate both sides of the equation with respect to ( x ).
- Apply the chain rule where necessary.
- Solve for ( \frac{dy}{dx} ).
Applying these steps, you get:
[ \frac{d}{dx}\left(\ln\left(\frac{x}{y}\right)\right) = \frac{d}{dx}(x - y) ]
[ \frac{1}{\frac{x}{y}}\left(\frac{d}{dx}\left(\frac{x}{y}\right)\right) = 1 - \frac{dy}{dx} ]
[ \frac{y}{x}\left(\frac{1}{y}\frac{dx}{dx} - \frac{x}{y^2}\frac{dy}{dx}\right) = 1 - \frac{dy}{dx} ]
[ \frac{1}{x} - \frac{x}{y^2}\frac{dy}{dx} = 1 - \frac{dy}{dx} ]
[ -\frac{x}{y^2}\frac{dy}{dx} + \frac{dy}{dx} = 1 - \frac{1}{x} ]
[ \left(1 - \frac{x}{y^2}\right)\frac{dy}{dx} = 1 - \frac{1}{x} ]
[ \frac{dy}{dx} = \frac{1 - \frac{1}{x}}{1 - \frac{x}{y^2}} ]
By signing up, you agree to our Terms of Service and Privacy Policy
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
- How do you differentiate #g(x) = (6x+9)(5x^6 - 4)# using the product rule?
- If #f(x) =-e^(2x-1) # and #g(x) = 2cos^2x #, what is #f'(g(x)) #?
- How do you differentiate #f(x)=11xe^(2x)# using the product rule?
- How do you differentiate #f(x)= -1 / (-2x-4 )# using the quotient rule?
- How do you find dy/dt given #y= 4 sin ( sqrt (1+ sqrt (x) ))#?
- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7